Dictogloss As An Interactive Technique In Teaching Writing Recount Text For Tenth Grade At Sma Antartika Sidoarjo (RETAIN, 2016)
Dictogloss As An Interactive Technique In Teaching Writing Recount Text For Tenth Grade At Sma Antartika Sidoarjo Ima Damayanti English Education Program, Faculty of Languages and Arts, State University of Surabaya imadamayanti@mhs.unesa.ac.id Nur Chakim, S.Pd., M.Pd English Education Program, Faculty of Languages and Arts, State University of Surabaya nurchakim@unesa.ac.id Abstrak Keahlian menulis merupakan salah satu dari kealiah-keahlian penting yang harus dikuasai siswa ketika mempelajari bahasa Inggris. Namun beberapa penelitian mengemukakan kesulitan yang dihadapi siswa dalam kegiatan menulis seperti kesulitan dalam mengatur dan mengembangkan ide juga kejenuhan yang menurunkan motivasi mereka dalam belajar. Maka dari itu, diperlukan teknik yang tepat yang mampu membantu siswa mengatur dan mengembangkan ide dalam menulis serta membuat mereka tetap menikmati kegiatan belajar. Dictogloss adalah kegiatan pendiktean yang dilakukan di kelas dimana guru membacakan sebuah teks, siswa mendengarkan teks tersebut, menuliskan kata kunci yang telah mereka dengarkan kemudian bekerja bersama untuk membuat teks rekonstruksi (Ruth Wajnryb, 1990). Penelitian kualitatif ini dilakukan untuk menjawab tiga pertanyaan penelitian. Pertanyaan pertanyan tersebut adalah; (1) Bagaimana implementasi teknik Dictogloss untuk mengajar keahlian menulis teks recount kelas sepuluh? (2) Bagaimanakah respon siswa terhadap implementasi teknik Dictogloss untuk mengajar keahlian menulis teks recount kelas sepuluh? (3) Bagaimana hasil kerja siswa setelah implementasi teknik Dictogloss untuk mengajar keahlian menulis teks recount kelas sepuluh?. Data yang ada diperoleh menggunakan beberapa instrumen diantaranya adalah observation checklist, fieldnotes, kuesioner, dan hasil kerja siswa berdasarkan rubrik ketrampilan menulis. Hasil dari penelitian implementasi teknik Dictogloss untuk mengajar keahlian menulis teks recount kelas sepuluh menunjukkan hasil yang baik. Dalam proses belajar, peneliti melihat bahwa banyak siswa memperhatikan instruksi guru dengan baik. Hasil dari kuesioner, ditemukan bahwa siswa setuju jika aktifitas Dictogloss menyenangkan dan memotivasi mereka untuk belajar. Hasil kerja siswa yang telah dinalisis juga menunjukkan hasil yang memuaskan dalam aspek konten, organisasi, kosa kata, penggunaan bahasa, dan ejaan serta tata tulis. Ini membuktikan bahwa teknik Dictogloss berhasil membantu siswa dalam mempelajari keahlian menulis teks recount dengan kegiatan yang menyenangkan. Kata Kunci: Teknik Dictogloss, ketrampilan menulis, teks recount Abstract Writing is one of the crucial skills the students need to master when they are learning english. Nevertheless, some study revealed students’s difficulties in writing activity such as the difficulty to organize and develop the ideas and also the boredom which decrease their motivation in learning. Therefore, it is needed the proper technique which help them organize the ideas in writing and also keep them enjoying the learning activity. Dictogloss is classroom dictation activity where teachers read the passage, the students listen to a passage, note down keywords they hear and then work together to create a reconstructed version (Ruth Wajnryb, 1990). This qualitative research was conducted to answer three research questions.The questions are; (1) How is the implementation of Dictogloss technique to teach writing recount text for tenth grade? (2) How are students’s responses toward the implementation of Dictogloss technique to teach writing skill recount text for students in tenth grade? (3) How is students’s tasks after the implementation of Dictogloss technique to teach writing recount text for students in tenth grade? The data were obtained by using some instruments such as observation checklist, fieldnotes, questionnaire, and student’s task based on writing rubric. The result of this research of the implementation of Dictogloss technique to teach writing skill recount text for tenth grade showed the satisfying result. In the process of learning, the researcher found that most of students paid attention well to the teacher instruction and explanation. The teacher had already succeeded in implementing Dictogloss technique in teaching writing skill recount text for tenth grade. From the questionnaire, it was found that students agreed that the activities in Dictogloss were enjoyable and motivated them to learn.The students’s tasks that had been analyzed also showed the satisfying results in terms of content, organization, vocabulary, language use, and mechanics. This is proved that Dictogloss successfully helped the students to learn writing skill recount text in the form of enjoyable activities. Keywords: Dictogloss technique, Writing Skill, Recount Text